Strategy for Improving Operational Management Efficiency in Islamic Higher Education Institutions: An Approach Integrating Technology and Local Wisdom - Dasep Supriatna (International Journal of Management and Business Economics, 2025)
Operational efficiency in Islamic Higher Education Institutions (IHEIs) requires the integration of technology that is aligned with local wisdom and Islamic values. This study, framed by Contingency Theory, aims to identify adaptive integrative strategies for institutional contexts. A qualitative case study was conducted on four IHEIs in Indonesia, selected based on geographical variation and institutional accreditation status. Data were collected through semi-structured interviews with 16 key informants (institutional leaders, heads of IT units, and faculty members), as well as analysis of 24 institutional policy documents and strategic plans. Thematic analysis was used to identify patterns of technology integration with Islamic values and local culture. The results show that the effectiveness of integration depends on the contextual conditions of each institution. For example, one institution integrated a digital learning management system with character-building modules based on Islamic boarding school values, while another institution adapted its digital platforms to the structure of the local traditional organization. Theoretical implications suggest the need for contingency-based managerial flexibility in Islamic education governance. Practical implications point to the importance of developing technology policies that are responsive to the religious and cultural values of institutions. This study confirms that the success of digital transformation in IHEIs is not solely determined by technological capacity, but by the institution's ability to adapt strategies to its socio-cultural and spiritual context.